The subunit assembly state of the Mediator complex is nutrient-regulated and is dysregulated in a genetic model of insulin resistance and obesity - Youn, Dou Yeon (J Biol Chem, 2019)
The Mediator complex plays a critical role in the regulation of transcription by linking transcription factors to RNA polymerase II. By examining mouse livers, we have found that in the fasted state, the Mediator complex exists primarily as an approximately 1.2-MDa complex, consistent with the size of the large Mediator complex, whereas following feeding, it converts to an approximately 600-kDa complex, consistent with the size of the core Mediator complex. This dynamic change is due to the dissociation and degradation of the kinase module that includes the MED13, MED12, cyclin-dependent kinase 8 (CDK8), and cyclin C (CCNC) subunits. The dissociation and degradation of the kinase module are dependent upon nutrient activation of mTORC1 that is necessary for the induction of lipogenic gene expression because pharmacological or genetic inhibition of mTORC1 in the fed state restores the kinase module. The degradation but not dissociation of the kinase module depends upon the E3 ligase, SCF(FBW7). In addition, genetically insulin-resistant and obese db/db mice in the fasted state displayed elevated lipogenic gene expression and loss of the kinase module that was reversed following mTORC1 inhibition. These data demonstrate that the assembly state of the Mediator complex undergoes physiologic regulation during normal cycles of fasting and feeding in the mouse liver. Furthermore, the assembly state of the Mediator complex is dysregulated in states of obesity and insulin resistance.